2018
DOI: 10.1002/hec.3627
|View full text |Cite
|
Sign up to set email alerts
|

EQ-5D-5L: Smaller steps but a major step change?

Abstract: ), potentially has important implications for technology coverage decision making in many jurisdictions around the world.The 5-level version of EQ-5D (EQ-5D-5L) was developed in response to criticism centring on questions of sensitivity of the original 3-level version; many patients would indicate no problems on all five dimensions (i.e., State 11111), despite many of these respondents reporting they do have problems on similar dimensions of other measures (Brazier, Ratcliffe, Tsuchiya, & Solomon, 2017). At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…For example, early considerations that require the systematic review of available evidence and/or developmental pilot work include evaluating the relative merits of using (1) line drawings compared with photographs, (2) images for every response option compared with images at the ends of the scale only, and (3) the same images in different clinical contexts. Once a new pictorial descriptive classification system has been developed, examination of measurement properties will be required, such as the assessment of practicality, reliability, responsiveness and validity [ 34 , 35 ]. The importance of comparability across studies and conditions was the primary reason for modifying EuroQol instruments rather than developing a new instrument.…”
Section: Contribution and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, early considerations that require the systematic review of available evidence and/or developmental pilot work include evaluating the relative merits of using (1) line drawings compared with photographs, (2) images for every response option compared with images at the ends of the scale only, and (3) the same images in different clinical contexts. Once a new pictorial descriptive classification system has been developed, examination of measurement properties will be required, such as the assessment of practicality, reliability, responsiveness and validity [ 34 , 35 ]. The importance of comparability across studies and conditions was the primary reason for modifying EuroQol instruments rather than developing a new instrument.…”
Section: Contribution and Future Directionsmentioning
confidence: 99%
“…Given the significant complexities of developing pictorial instruments compared with more conventional text-based instruments, a further important issue is whether there is a need for three-level and five-level pictorial variants. Such decisions will be influenced, to some extent, by the current research and debate surrounding the role of the EQ-5D-5L in health technology assessment [ 34 , 35 ].…”
Section: Contribution and Future Directionsmentioning
confidence: 99%
“…The first UK valuation study of the 5L descriptive system was formally available in 2017 [4]. As Brazier, Bryan and Briggs recently summarize [5], the 5L version of the instrument has been found to reduce ceiling effects and exhibits a more even distribution of responses. Hernandez et al [6] have shown that as a consequence of the changes to the tool and the new valuation system, utility scores derived using the 5L version are compressed towards the full health end of the measurement scale, suggesting that while the 5L version describes more distinct health states, the values placed on them are potentially less sensitive for detecting clinically meaningful changes in health utility.…”
Section: The Eq-5d-5lmentioning
confidence: 99%
“…Would it solve a problem not solved by a competing tool? In a competitive marketplace, would adoption of the 5L tool be justified, given its already contested descriptive system and valuation study [5]? Or would a different instrument be preferred?…”
Section: Proceed With Cautionmentioning
confidence: 99%
“…Moreover, the impact of using one utility estimation method over the other on the statistical uncertainty surrounding cost–utility estimates is still unclear. The latter is particularly important as it provides insight into the validity of reimbursement decisions based on economic evaluations that relied on interim crosswalk QALY estimates (Brazier, Briggs, & Bryan, ).…”
Section: Introductionmentioning
confidence: 99%